A 7-Tesla MRI study of the periaqueductal gray: resting state and task activation under threat. Issue 2 (9th July 2021) - Weis, Carissa N; Bennett, Kenneth P; Huggins, Ashley A; Parisi, Elizabeth A; Gorka, Stephanie M; Larson, Christine
Abstract: The periaqueductal gray (PAG) is a region of the midbrain implicated in a variety of behaviors including defensive responses to threat. Despite the wealth of knowledge pertaining to the differential functional roles of the PAG columns in nonhuman and human research, the basic functional connectivity of the PAG at rest has not been well characterized. Therefore, the current study utilized 7-Tesla magnetic resonance imaging (MRI) to characterize PAG functional connectivity at rest and task activation under uncertain threat. A sample of 53 neurologically healthy undergraduate participants (Mage = 22.2, s.d.age = 3.62) underwent structural and resting state functional MRI scans. Supporting previous work, voxel-wise analyses showed that the PAG is functionally connected to emotion regulation and fear networks. The comparison of functional connectivity of PAG columns did not reveal any significant differences. Thirty-five participants from the same sample also completed an uncertain threat task with blocks of three conditions—no shock, predictable shock and unpredictable shock. There were no robust activity differences within the PAG columns or the whole PAG across conditions although there was differential activity at the voxel level in the PAG and in other regions theoretically relevant to uncertain threat. Results of this study elucidate PAG connectivity at rest and activation in response to uncertain threat.